2021
DOI: 10.1177/20571585211066018
|View full text |Cite
|
Sign up to set email alerts
|

Competence of clinical nurse educators in university hospitals: A cross-sectional study

Abstract: The role of clinical nurse educators is essential in improving the quality of mentoring, supporting students’ learning and professional development during clinical training. The purpose was to explore the competence profiles of clinical nurse educators and background factors associated with these profiles. Data of this cross-sectional study were collected from clinical nurse educators ( n = 19) at Finnish university hospitals, using two instruments measuring the competence of healthcare educators. Data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This underscores the importance of educational qualifications in shaping the competency landscape among healthcare professionals in infection prevention and control. It has been found that clinical nurse educators with higher levels of education and greater lengths of work experience often report higher self-assessed levels of competence, highlighting the impact of educational backgrounds on competence levels [ 19 ].Institutions and policymakers should recognize the pivotal role of educational backgrounds, encouraging and facilitating continuous learning to ensure a skilled and competent IPC workforce capable of addressing evolving healthcare challenges.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the importance of educational qualifications in shaping the competency landscape among healthcare professionals in infection prevention and control. It has been found that clinical nurse educators with higher levels of education and greater lengths of work experience often report higher self-assessed levels of competence, highlighting the impact of educational backgrounds on competence levels [ 19 ].Institutions and policymakers should recognize the pivotal role of educational backgrounds, encouraging and facilitating continuous learning to ensure a skilled and competent IPC workforce capable of addressing evolving healthcare challenges.…”
Section: Discussionmentioning
confidence: 99%